Copaifera officinalis oil cytoprotector and antisecretory effects in induced gastric lesions in rats - Arroyo, Jorge (2009)
Objetives: To determine the gastroprotector effect of Copaifera officinalis oil using indomethacin and pyloric ligature in rats. Design: Preclinical study. Setting: Faculties of Medicine, Pharmacy and Biochemistry, National University of San Marcos, Lima, Peru. Biological material: Rats and copaiba oil. Interventions: Copaiba oil was collected in Ucayali, Pucallpa. Cytoprotection was tested with indomethacin considering a normal control group, and indomethacin, copaiba and omeprazole groups. Using visual analogue scale mucosa gastric injuries were referred as those compatible with local necrosis (unviable tissue), hyperemia, flushing, and hemorrhage, and ulcers according to the modified Macallister’s scale. The anti-secretion trial used the pyloric ligature model. Twenty-four albino rats were randomized in three groups: control, copaiba oil 40 mg/kg and omeprazole 10 mg/kg, respectively. After 4 hours of linkage, they were sacrificed. Stomachs were removed, their volume measured carefully and gastric secretion pH determined by potentiometry. Devis’s histopathological evaluation was used. Main outcome measures: Ulcerous injuries. Results: There was 100% cytoprotection with copaiba oil and 97,8% with omeprazole (p<0,0001), ratified by histological findings. Decrease in secretion volume was 79,4% for omeprazole and 42,8% for copaiba oil (p<0,0001) with pH increment. Conclusions: In experimental conditions copaiba oil was effective as gastroprotective agent in gastric ulcers-induced rats.